Adsorção de Cd2+, Ni2+ e Zn2+ em soluções aquosas usando anidrita e lama vermelha - da Conceição, Fabiano Tomazini [UNESP]; Pichinelli, Beatriz Cestaro [UNESP]; da Silva, Mariana Scicia Gabrial [UNESP]; Antunes, Maria Lúcia Pereira [UNESP]; Lopes, Mayara Sakamoto [UNESP]; Moruzzi, Rodrigo Braga [UNESP] (FapUNIFESP (SciELO), 2017)
Various minerals and industrial waste have been studied for use as an adsorbent, in particular the anhydrite and the red mud. The red mud is an insoluble residue that is generated in large quantities during the processing of bauxite. The anhydrite is a calcium sulfate (CaSO4), crystallized as a rhombic way, and used as raw material in the industry. In this study, the Cd2+, Ni2+ and Zn2+adsorption capacity by anhydrite and by red mud was evaluated using adsorption isotherms obtained by the Langmuir and Freundlich models. The materials used showed adsorption ≥75±1% for all metals in aqueous solutions with a concentration of 0.5 mmol.25 mL-1. The Langmuir isotherm was more appropriate to describe the phenomenon of Cd2+, Ni2+ and Zn2+ removal, with highest adsorption capacity at 0.47 and 0.51 mmol.g-1 for Cd2+, 1.18 and 1.56 mmol.g-1 for Ni2+, and 0.84 and 1.47 mmol.g-1 for Zn2+, respectively. These values were higher than those ones obtained for other materials described in previous studies.
Adsorption of Cd2+, Ni2+ and Zn2+ in aqueous solutions using anhydrite and red mud
Keywords: Anhydrite; Metals; Red mud; Wastewater treatment